Marriage, wealth, and unemployment duration: a gender asymmetry puzzle - Rasmus Lentz; Torben Tranæs (Institute for the Study of Labor (IZA), 2005)
This note presents evidence of the following gender asymmetry: the job-finding effort of married men and women is affected by the income of their spouses in opposite directions. For women, spouse income influences job finding negatively, just as own wealth does: the more the man earns and the wealthier the woman is, the longer it takes for her to find a job. The contrary is the case for men, where spouse income affects job finding positively: the more the wife earns, the faster the husband finds a job. This is so despite the fact that greater own wealth also prolongs unemployment spells for men. These findings are hard to reconcile with the traditional economic model of the family.
Keywords: D1; J4; J6; 330; gender asymmetries; wealth effects on job finding; unemployment duration